Improvement of pickled mangoes - Bermas, Donna Bliss B.; Rillo, Belen O. (1982., 1982)
The improvement of pickled mangoes was undertaken concerning texture, flavor, and keeping-quality. Green immature mangoes of the Pico and Carabao varieties and salt level of 7% and 10% were employed. Objective tests and sensory evaluation results showed a greater acceptability in terms of flavor for Pico mangoes pickled in 10% brine. Alum and calcium chloride were compared as firming agents of pickled Pico mangoes. Texture difference tests and penetrometer readings revealed that 1% calcium chloride is a better firming agent for pickled Pico mangoes. Two heat treatments, flash pasteurization with a temperature of 160°F for 154 seconds and hot-packing in a syrup of 180°F, were compared for keeping quality of the pickled mangoes. Microbiological tests and penetrometer readings showed that the flash pasteurization treatment is better for bottled mangoes.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mango